Nature-inspired micro/nanomotors. Issue 2 (22nd December 2021) - Chang, Xiaocong; Feng, Yiwen; Guo, Bin; Zhou, Dekai; Li, Longqiu
Abstract : We provide an overview of various nature-inspired micro/nanomotors through summarizing the natural morphology-inspired micro/nanomotors, natural structure-inspired micro/nanomotors and versatile micro/nanomotors with nature-inspired behaviors. Abstract : Living things in nature have evolved with unique morphologies, structures, materials, behaviors, and functions to survive in complex natural environments. Nature has inspired the design ideas, preparation methods, and applications of versatile micro/nanomotors. This review summarizes diverse nature-inspired micro/nanomotors, which can be divided into five groups: (i) natural morphology-inspired micro/nanomotors, whose shapes are designed to imitate the morphologies of plants, animals, and objects in nature. (ii) Natural structure-inspired micro/nanomotors, which use structures from plants, red blood cells, and platelet cells as components of micro/nanomotors, or directly use sperm cells and microorganisms as the engines of micro/nanomotors. (iii) Natural behavior-inspired micro/nanomotors, which are proposed to mimic natural behaviors such as motion behavior, swarm behavior, and communication behavior between individuals. (iv) Micro/nanomotors inspired by both natural morphology and behavior. Nature makes it possible for synthetic micro/nanomotors to possess interesting morphologies, novel preparation methods, new propulsion modes, innovative functions, and broad applications. The nature-inspired micro/nanomotors could provide a promising platform for various practical fields.